Vascular epiphytes show low physiological resistance and high recovery capacity to episodic, short‐term drought in Monteverde, Costa Rica. (12th July 2020) - Williams, Cameron B.; Murray, Jessica G.; Glunk, Andrew; Dawson, Todd E.; Nadkarni, Nalini M.; Gotsch, Sybil G.
Abstract: Tropical montane cloud forests support abundant epiphytic vascular plant communities that serve important ecosystem functions, but their reliance on atmospheric inputs of water may make them susceptible to the drying effects of rising cloud bases and more frequent droughts. We conducted a common garden experiment to explore the combined effects of decreasing cloud influence—lower humidity, warmer temperature, brighter light—and meteorological drought (i.e. absence of rain) on the physiology and morphology of vascular epiphytes native to primary forests of Monteverde, Costa Rica. The epiphytes, which exhibited C3 photosynthesis, were sourced from a lower montane cloud forest (CF) or a rainforest (RF) below the current cloud base and transplanted into nearby shadehouses (CF or RF shadehouse respectively). Vapour pressure deficit (VPD) and light availability, measured as photosynthetically active radiation, were 2.5 and 3.1 times higher in the RF than the CF shadehouse. Half of the plants were subjected to a severe 4‐week drought followed by a recovery period, and the other half were watered controls. Plants subjected to low VPD/light conditions of the CF shadehouse were physiologically and morphologically resistant to the drought treatment. However, compared to control plants, both sources of plants subjected to high VPD/light conditions of the RF shadehouse experienced declines in maximum net photosynthesis ( A max ), stomatal conductance ( g s ) and the proportion of healthy leaves (those not exhibiting chlorosis, desiccation or necrosis). At peak drought, leaves from the RF were 19% thinner than controls. Within 7–14 days after rewatering, A max, g s and leaf health recovered to nearly the levels of controls. Growth rate, mortality and phenology were unaffected by the treatments. The divergent responses to drought in the CF versus RF shadehouses, combined with the recovery in the RF shadehouse, indicate that these epiphytes possess adaptive properties that confer low resistance, but high recovery capacity, to episodes of short‐term drought over a range of cloud influence. In addition, the reduction in A max suggests stomatal regulation that favours water conservation over carbon acquisition, a strategy that may inform epiphyte responses to rising clouds and increasing drought frequency expected in the long term. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article .